2014
DOI: 10.1103/physreve.89.013312
|View full text |Cite
|
Sign up to set email alerts
|

Robust computation of dipole electromagnetic fields in arbitrarily anisotropic, planar-stratified environments

Abstract: We develop a general-purpose formulation, based on two-dimensional spectral integrals, for computing electromagnetic fields produced by arbitrarily oriented dipoles in planar-stratified environments, where each layer may exhibit arbitrary and independent anisotropy in both its (complex) permittivity and permeability tensors. Among the salient features of our formulation are (i) computation of eigenmodes (characteristic plane waves) supported in arbitrarily anisotropic media in a numerically robust fashion, (ii… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(99 citation statements)
references
References 28 publications
(110 reference statements)
0
99
0
Order By: Relevance
“…Recent studies have shown that this problem can be circumvented through suitable rescaling of various expressions involved in the computational chain [50,52], as well as expressing by the ratios of Bessel or Hankel functions [53]. The LWD tools modeled in this dissertation do not required high orders cylindrical functions, but for extreme conductivity media the techniques reported in [50,52,53] need to be used.…”
Section: Axial Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that this problem can be circumvented through suitable rescaling of various expressions involved in the computational chain [50,52], as well as expressing by the ratios of Bessel or Hankel functions [53]. The LWD tools modeled in this dissertation do not required high orders cylindrical functions, but for extreme conductivity media the techniques reported in [50,52,53] need to be used.…”
Section: Axial Fieldsmentioning
confidence: 99%
“…This problem comes from the complex large argument of the cylindrical functions. In that situations, we could consider approximated impedance boundary condition (as those proposed in Section 3.3.3.1) and also the rescaling of Bessel functions (recently proposed in [50,52,53]) to prevent this numerical problem.…”
Section: Conclusion and Suggestions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of dipole radiation in optically anisotropic layered media without spatial dispersion has been previously considered using the Green function formalism [19][20][21][22][23][24]. When using the formalism, the materials are described by single electric permittivity and magnetic permeability tensors.…”
Section: Verificationmentioning
confidence: 99%
“…However, they only determine the field in some specific types of materials, including homogeneous anisotropic materials [19][20][21][22][23][24], lossless photonic crystals with known Bloch modes [25], and one-dimensional nanomaterials, such as dielectric-metal stacks [26]. More complex media, especially spatially dispersive ones, are out of reach of these methods.…”
Section: Introductionmentioning
confidence: 99%